APPRAISAL ATTITUDE ON EDITORIAL NEWS: OUR DISASTROUS PRESIDENT - Susanto, Dias Andris; Bimo, Djoko Sri (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
Appraisal Theory's linguistic discourse analysis gives different techniques to analyze "objectivity" and ideological bias in news editorial. Systemic Functional Linguistics (SFL) describes the way in which language constructs attitude, and allows speakers or writer to place themselves in relation to prospective responses or other speakers/writers in terms of how they value their opinions. The study was aimed to know existing of appraisal attitude system in news editorial and to figure out the dominant types of appraisal in the Los Angeles Times News Editorial convey the meaning of the sentence. The writer look at the creation of journalistic reality from a linguistic point of view, how the choices journalists make in terms of vocabulary reveal their ideological standing, both in terms of content and context. For this purpose the writers using the Los Angeles Times editorial which published in January 17th 2021 as an example, this chapter applies the framework an appraisal. Since these articles make connection to President Donald J. Trump. It activate powerful evaluation of appraisal attitude values that provide news articles evaluative implications that observed. The news editorial system draws attention to the importance of emotion, judgment and appreciation in its coverage of problems. As a results, the study showed that performance in appraisal system in Los Angeles Times news editorial is almost in entire text the writer give some lexical items that give “affect” to the reader. In this case is negative affect. And then, the writer intends to give less attention on appreciation lexical items.